Karakter dan Potensi Inokulum Bakteri Fosfat dalam Melepaskan Fosfor - Tamad Tamad (Fakultas Biologi | Universitas Jenderal Soedirman, 2014)
Soil bacteria group which can release soil P-adsorbed is phosphate bacteria (PB). PB can release soil P-adsorbed through: 1) acidification, 2) chelating 3) ligand exchange 4) mineralization and 5) compete colloid sorption site. PB have a potential to release soil P-adsorbed. This study was aimed to determining the character and PB inoculant potential in soil P-adsorbed release. The results of BLASTn PB showed that isolate 1 was Pseudomonas trivialis, isolate 5 was Pseudomonas putida and isolate 9 was Pseudomonas fluorescens. Based on the growth curve on day 5th (the end log. phase) population of Pseudomonas trivialis was 1010 CFU/mL, Pseudomonas putida was 1014 CFU/mL and Pseudomonas fluorescens was 1017 CFU/mL. Storage inoculant PB population decrease 97-84 % and 80-65 % PB lowering capabilities.